The Correlation of Hba1c Level With GSH-PX Enzyme Activity, AOPP, and MDA Levels in The Eye Lenses of Diabetic Cataract Patients - Maria Winney Natania; Monica Claudia; Refita Maharani; Muhammad Ali Faisal; Triawanti Triawanti (Berkala Kedokteran, 2020)
Abstract: Diabetes Mellitus (DM) is known to accelerate cataractogenesis because it may cause hyperglycemia-induced stress oxidative in the eye lens. HbA1c test can be performed to monitor glycemic control. Glutathione peroxidase (GSH-Px) is an enzyme that scavenges and prevents the formation of free radical. Advanced Oxidation Protein Products (AOPP) is a marker to estimate the degree of oxidative protein modification. Malondialdehyde (MDA) can reflect cells damage. This study was an observational analytic study, conducted in September 2019-January 2020, and aimed to determine the correlation of HbA1c level with GSH-Px enzyme activity, AOPP, and MDA levels in the eye lenses of diabetic cataract patients. Data of HbA1c level and eye lenses sample was obtained from 29 cataract patients with DM who underwent phacoemulsification surgery in Ulin and Bhayangkara Hospital in Banjarmasin and fulfilled the inclusion criteria. Spearman’s correlation test showed that there was no significant correlation of HbA1c with GSH-Px activity (p=0,095), AOPP (p=0,084), and MDA (p=0,084) levels in the eye lens of diabetic cataract patients. Keywords: Diabetes mellitus, cataract, HbA1c, glutathione peroxidase, AOPP, MDA